Increased expression of PDIA3 and its association with cancer cell proliferation and poor prognosis in hepatocellular carcinoma - Takata, Hideyuki (Oncol Lett, 2016)
The prognosis of hepatocellular carcinoma (HCC) is unfavorable following complete tumor resection. The aim of the present study was to identify a molecule able to predict HCC prognosis through comprehensive protein profiling and to elucidate its clinicopathological significance. Comprehensive protein profiling of HCC was performed by liquid chromatography-tandem mass spectrometry. Through the bioinformatic analysis of proteins expressed differentially in HCC and non-HCC tissues, protein disulfide-isomerase A3 (PDIA3) was identified as a candidate for the prediction of prognosis. PDIA3 expression was subsequently examined in 86 cases of HCC by immunostaining and associations between PDIA3 expression levels and clinicopathological characteristics were evaluated. The Ki-67 index and apoptotic cell death of carcinoma cells were examined by immunostaining and terminal deoxynucleotidyl transferase dUTP nick-end labeling assay in 24 cases. The results demonstrated that PDIA3 was expressed in all 86 HCC cases; 56 HCC cases (65%) exhibited high expression of PDIA3 and 30 (35%) exhibited low expression. The disease-free and overall survival times of HCC patients with high PDIA3 expression were significantly shorter than in HCC patients with low expression. Furthermore, increased expression of PDIA3 was associated with an elevated Ki-67 index, indicating increased cancer cell proliferation and a reduction in apoptotic cell death. Taken together, these results suggest that PDIA3 expression is associated with tumor proliferation and decreased apoptosis in HCC, and that increased expression of PDIA3 predicts poor prognosis. PDIA3 may therefore be a key molecule in the development of novel targeting therapies for patients with HCC.